LA PARTICIPACIÓN DEL CLERO COSTARRICENSE EN LAS CAMPAÑAS POLÍTICAS DE 1889 Y 1894 - Solano Muñoz, Edgar (2010)
The article analyzes the role the Church through fractions of the clergy play in the political campaigns of Costa Rica in 1889, 1892 and 1894. Particular attention is paid to the political behavior of clergy from the Catholic formation of the Union Party. In sum, the linking of the clergy to political-electoral activity was prompted by two main reasons: the return of religious education in schools funded by the state and safeguarding the interests of the monastic orders in Costa Rica.